Determinants of Health in Abrahamic Scriptures: A Comparative Thematic Analysis of the Quran, Bible, and Torah - Belay Sitotaw Goshu; Muhammad Ridwan (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
Mainstream models of health determinants, including the Dahlgren Whitehead rainbow model and WHO frameworks, overlook spiritual and religious factors despite growing evidence of their influence on health outcomes. Abrahamic scriptures the Quran, Bible, and Torah contain extensive guidance on health, yet no systematic comparative analysis has mapped their determinants. This study aimed to identify, categorise, and compare health determinants articulated in the Quran, Bible, and Torah, and to integrate findings into contemporary public health discourse. A comparative qualitative thematic analysis was conducted. Deductive codes were derived from existing determinant models; inductive codes emerged from scriptural analysis. Texts included the Quran (Arabic with Saheeh International translation), the Bible (NIV/NRSV), and the Torah (Jewish Publication Society translation). Rigour was ensured through audit trails, peer debriefing, and negative case analysis. Four determinant categories were identified: metaphysical (divine will, sin, spiritual forces, prayer), behavioural (diet, hygiene, rest, sexual ethics, intoxicants), social (charity, community responsibility, justice, governance), and psychological (faith, gratitude, repentance). All three scriptures affirm metaphysical determinants. Behavioural determinants are strongest in the Quran and Torah; social determinants are strongest in the Bible; psychological determinants are strong in the Quran and Bible, moderate in the Torah. Conclusion: Abrahamic scriptures present a holistic model in which the divine human relationship is the primary health determinant, extending beyond secular frameworks. Public health practice should integrate spiritual determinants through culturally competent promotion, faith based interventions, and clinical spiritual assessment. Future research should quantify scriptural determinants and extend analysis to other religious traditions.